Assessment and comparison of heavy metal concentration in fruit and vegetable samples of market and roadside vendors (International Journal of Food and Nutritional Sciences, 2024)
Abstract: Consumption of Fruits and vegetables contaminated with heavy metals can accumulate in different body parts and cause chronic diseases affecting vital organs of the body. Hence, a comparision study was carried out to analyse the presence of heavy metals in fruit and vegetable samples collected from roadside and market vendors. The concentration of heavy metals such as arsenic (As), cadmium (Cd), copper (Cu), lead (Pb), and mercury (Hg) were analysed using inductively coupled plasma-mass spectrometry (ICP-MS). The result showed that the heavy metal concentration of apple samples obtained from the market and roadside are 0.057, 0.070, 0.233, 0.200, 0.053 and 0.077, 0.070, 0.200, 0.300, and 0.073 for As, Cd, Cu, Pb and Hg respectively. For capsicum, the concentrations of market and roadside samples were 0.077, 0.063, 0.200, 0.367, 0.070 (µg/kg) and 0.067, 0.077, 0.200, 0.267 and 0.047 (µg/kg) for As, Cd, Cu, Pb and Hg respectively. The study concluded that the concentration of metals such as As, Pb and Hg were higher in the apple sample obtained from roadside vendors than in the market sample. On the other hand, the concentrations of As, Pb and Hg were higher in the capsicum obtained from the market than from the roadside vendors. Though the heavy metals concentration in fruit and vegetable samples collected from roadside vendors and markets were within the permissible levels recommended by WHO/ FAO, continuous ingestion for a longer period can pose potential side effects.